What Does It Mean to Be a Science Librarian 2.0? - Missy Harvey (Issues in Science and Technology Librarianship, 2009)
Science librarians, as well as other librarians, have seen ample new technologies come and go over the years. Librarians experiment and try to find ways to employ the new tools in our libraries. A driving force in our decision making about what tools to use should always be our patrons and whether the tools can help us do a better job of delivering services. This paper discusses what technologies have proven to be successful, as well as other thoughts to bear in mind as librarians evaluate Web 2.0 tools for science libraries. [ABSTRACT FROM AUTHOR]